Detection and verification of QTLs associated with heat-induced quality decline of rice (Oryza sativa L.) using recombinant inbred lines and near-isogenic lines - Kobayashi, Asako (Breeding science, 2013)
Decline in the apparent quality of rice (Oryza sativa L.) grain due to high temperatures during ripening recently became a major concern in many areas in Japan. The occurrence of white-back kernels (WBK) is one of the main problems of heat-induced quality decline. We identified QTLs associated with the occurrence of WBK using recombinant inbred lines (RILs) and verified their effects using near-isogenic lines (NILs). The QTL analysis used F7 and F8 RILs derived from 'Hana-echizen' (HE), which is tolerant to high temperature, × 'Niigata-wase' (NW), which is sensitive to high temperature. Four QTLs were identified on chromosomes 3, 4, 6, and 9 (qWB3, qWB4, qWB6 and qWB9). To verify the effects of qWB6 and qWB9, we developed two NILs in which qWB6 or both were introduced from HE into the NW background. The HE allele at qWB6 significantly decreased WBK under multiple environments. The combination of qWB6 and qWB9 in an F2 population derived from a cross between a NIL and NW showed that the NW allele at qWB9 significantly decreased WBK if the qWB6 allele was HE. These results will be of value in marker-assisted selection for the breeding of rice with tolerance to heat-induced quality decline